Intrasinusoidal Hodgkin Lymphoma; A Mimic of Anaplastic Large Cell Lymphoma - Krause, John R.; Fowler, James; Gill, Javed I. (Case Reports in Hematology, 2021)
The distinction between classical Hodgkin lymphoma (HL) and anaplastic large cell lymphoma (ALCL) is not problematic in most instances. In rare situations, HL may present with a sinusoidal infiltrative pattern that may mimic ALCL. It is important to use a battery of immunohistochemical stains to differentiate between these two entities as therapy and clinical behavior are different. We present a case of a young woman who presents with the very unusual intrasinusoidal infiltrative pattern.